1982
DOI: 10.1007/bf00545971
|View full text |Cite
|
Sign up to set email alerts
|

Modification in the pharmacokinetics of amikacin during development

Abstract: The disposition kinetics of a single i.v. dose of amikacin was studied in 6 neonates (6-25 days old), 10 infants (4-18 months) and 8 young children (3-11 years). There was a progressive change in the distribution and elimination kinetics during development. The distribution coefficient of the antibiotic averaged of 0.429, 0.320 and 0.210 l/kg in the newborns, infants and young children, respectively and serum half-life (t1/2 beta) in these three groups averaged 2.812, 1.803 and 1.196 h, respectively. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For infants and children, the manufacturer recommends a dose of 15 mg/kg/day administered intravenously or intramuscularly and divided into two or three doses. For neonates, a loading dose of 10 mg/kg followed by a maintenance dose of 7.5 mg/kg every 12 h administered intravenously over 1 to 2 h has been recommended by the manufacturer, as V of amikacin is higher in neonates than in infants and children (26,45). However, many other regimens have been proposed (23,41,45).…”
Section: Methodsmentioning
confidence: 99%
“…For infants and children, the manufacturer recommends a dose of 15 mg/kg/day administered intravenously or intramuscularly and divided into two or three doses. For neonates, a loading dose of 10 mg/kg followed by a maintenance dose of 7.5 mg/kg every 12 h administered intravenously over 1 to 2 h has been recommended by the manufacturer, as V of amikacin is higher in neonates than in infants and children (26,45). However, many other regimens have been proposed (23,41,45).…”
Section: Methodsmentioning
confidence: 99%
“…Although this was a relatively minor model adjustment for fosfomycin, amikacin required a more significant model modification to capture the change in neonatal V d seen from observed data. This change in amikacin V d as neonates age is well‐documented, 45 but the mechanism is not understood. Further characterization of this mechanism is required in order to incorporate this more generally in pediatric PBPK models.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the predictivity of the preterm PBPK model, two model drugs were selected based on the (i) the availability of clinical data in preterm neonates and (ii) differences in drug distribution and elimination behavior. While amikacin is a renally cleared antibiotic with relatively low distribution volume (approximately 0.25 -0.50 L/kg in adults [55]), the analgesic drug paracetamol mainly undergoes hepatic metabolization and distributes to a greater extent to peripheral compartments (distribution volume in adults around 1 L/kg [56]). The comparison of predicted plasma levels with TDM data obtained in the clinic for both drugs indicated that the physiologically-based model is indeed able to accurately predict the pharmacokinetics in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%